Thermoelectric material and method for producing the same

JP7637969B2Active Publication Date: 2025-03-03TOHOKU UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021023528
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-17
Publication Date
2025-03-03
Estimated Expiration
2041-02-17

AI Technical Summary

Benefits of technology

【0009】 本発明の上記態様によれば、高い出力因子PFと低い熱伝導率を両立し、優れた無次元性能指数zTを有するMg-Sn系の熱電材料および熱電材料の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637969000001
    Figure 0007637969000001
Patent Text Reader

Abstract

To provide a Mg-Sn based thermoelectric material which can achieve both of a high-output factor PF and low heat conductivity, and has a superior dimensionless performance index zT.SOLUTION: A thermoelectric material disclosed herein comprises Mg, Sn, and a doping element X for doping with carriers, which is a monocrystal material composed of a single crystalline, and in which α, a percentage of hole defects of Mg is over 0% and equal to or less than 20.0%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoelectric material and a method for making the thermoelectric material. [Background technology]

[0002] Thermoelectric materials that can generate electrical energy from waste heat are being developed. Known examples of thermoelectric materials include Bi2Te3 and PbTe. However, the constituent elements of conventional thermoelectric materials are rare, and elements such as Te have problems such as high toxicity.

[0003] Mg-Sn thermoelectric materials, which are made of Mg and Sn, are low-toxicity and inexpensive thermoelectric materials. Mg2Sn, a Mg-Sn thermoelectric material, has a problem of low dimensionless figure of merit zT, which indicates the performance of a thermoelectric material, due to its low electrical conductivity and high thermal conductivity. Here, zT is expressed as PF×T / κ, where PF is the power factor, T is the absolute temperature, and κ is the thermal conductivity.

[0004] As a technique for improving the zT of Mg-Sn based thermoelectric materials, Non-Patent Document 1 discloses Mg2Sn in which the thermal conductivity is reduced by introducing Mg vacancy defects. [Prior art documents] [Patent documents]

[0005] [Non-Patent Document 1] W. Saito, K. Hayashi, J. Dong, J.-F. Li and Y. Miyazaki, “Control of the Thermoelectric Properties of Mg2Sn Single Crystals via Point-Defect Engineering”, Sci. Rep., 10, 2020 (2020). Summary of the Invention [Problem to be solved by the invention]

[0006] However, the Mg2Sn of Non-Patent Document 1 has a problem in that the power factor PF decreases due to the introduction of Mg vacancy defects.

[0007] The present invention has been made in consideration of the above problems, and has an object to provide an Mg-Sn-based thermoelectric material that combines a high power factor PF with low thermal conductivity and has an excellent dimensionless figure of merit zT, and a method for manufacturing such a thermoelectric material. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention proposes the following means. <1> A thermoelectric material according to one embodiment of the present invention is a single crystal body that contains Mg, Sn, and a doping element X that dopes a carrier, and is made of a single crystal, and α, which is a ratio of vacancy defects in the Mg, is 8.9% or more , 18.0 % or less and further contains a pressure-applying element Z having an atomic radius smaller than the atomic radius of any one of the Mg, Sn, and doping element X, and the pressure-applying element Z is at least one of B, Li, Na, Cu, Zn, Ge, and Ag. <2 >Above <1> To In the described thermoelectric material, the doping element X may be at least one of Cu, Y, In, Sb, Bi, and La. < 3 >Above <1> To In the described thermoelectric material, the doping element X may be at least one of Li, Na, and Ag. <4 >Above< 1 > To In the described thermoelectric material, the molar ratio (Mg:Sn:X:Z) of the Mg, the Sn, the doping element X, and the pressure applying element Z satisfies any one of the following formulae (4) to (7), and may also satisfy the following formula (8): Mg:Sn:X:Z=2×(100-α) / 100:1-ab:a:b···(4)Mg:Sn:X:Z=2×(100-α) / 100-ab:1:a:b···(5)M g:Sn:X:Z=2×(100-α) / 100-a:1-b:a:b···(6)Mg:Sn:X:Z=2×(100-α) / 100-b:1-a:a:b···(7) 0 <a≦0.05、0<b≦0.05···(8) < 5 A method for producing a thermoelectric material according to one aspect of the present invention includes mixing at least Mg, Sn, and a doping element X for doping a carrier to prepare a mixture, and then heating the mixture in an inert gas until the temperature of the mixture reaches a melting temperature, thereby melting the mixture. After the mixture is melted, a pressure p [atm] of the inert gas satisfies the following formula (9), and an average cooling rate from the melting temperature to a slow-cooling stop temperature of the mixture is 2.5K / h or more 10.0 K Cooling to below / h The mixture further contains a pressure-applying element Z having an atomic radius smaller than that of any one of the Mg, Sn, and doping element X, and the pressure-applying element Z is at least one of B, Li, Na, Cu, Zn, Ge, and Ag. . 1.3 ≦p≦48 (9) <6 >Above< 5 > To In the method for producing a thermoelectric material described, the doping element X may be at least one of Cu, Y, In, Sb, Bi, and La. < 7 >Above< 5 > To In the method for producing a thermoelectric material described, the doping element X may be at least one of Li, Na, and Ag. <8 >Above< 5 > To In the method for producing a thermoelectric material described above, the molar ratio (Mg:Sn:X:Z) of the Mg, the Sn, the doping element X, and the pressure applying element Z satisfies any one of the following formulae (14) to (17), and may also satisfy the following formulae (18) and (19): Mg:Sn:X:Z=d:1-ab:a:b (14) Mg:Sn:X:Z=dab:1:a:b (15) Mg:Sn:X:Z=da:1-b:a:b (16) Mg:Sn:X:Z=db:1-a:a:b (17) 1.8≦d≦2.2 (18) 0 <a≦0.05、0<b≦0.05···(19) < 9 >Above< 5 >~<8 In the method for producing a thermoelectric material according to any one of the above items >, the melting temperature may be 1363K to 1042K. < 10 >Above< 5 >~< 9 In the method for producing a thermoelectric material according to any one of the above items >, the slow cooling stop temperature may be 1041K to 973K. < 11 >Above< 5 >~< 10 In the method for producing a thermoelectric material according to any one of the above items > to > , the pressure p may satisfy the following formula (20). 1.6≦p≦48 (20) Effect of the Invention

[0009] According to the above-described aspects of the present invention, it is possible to provide an Mg—Sn-based thermoelectric material that achieves both a high power factor PF and low thermal conductivity and has an excellent dimensionless figure of merit zT, and a method for manufacturing such a thermoelectric material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Thermoelectric materials> A thermoelectric material according to an embodiment of the present invention contains Mg, Sn, and a doping element X that dopes a carrier, and is a single crystal body made of a single crystal, in which α, which is a ratio of vacancy defects in Mg, is greater than 0% and less than or equal to 20.0%.

[0011] (Contains Mg, Sn, and a doping element X that dopes the carrier) The thermoelectric material according to this embodiment contains Mg, Sn, and a doping element X that dopes the carriers. Since the thermoelectric material according to this embodiment contains Mg and Sn, it is low-cost and has low toxicity. In addition, the thermoelectric material according to this embodiment has a low-temperature vacancy defect (V Mg) forms aggregates (clusters) and can increase phonon scattering. Furthermore, the doping element X also increases phonon scattering, making it possible to further reduce the thermal conductivity. In addition, the inclusion of the doping element X dopes the carriers, improving the power factor PF.

[0012] The doping element X in the thermoelectric material according to this embodiment is preferably at least one of Cu, Y, In, Sb, Bi, and La. When the doping element X is at least one of Cu, Y, In, Sb, Bi, and La, the electron carrier can be doped. As the doping element X, Sb is particularly preferable.

[0013] The doping element X in the thermoelectric material according to this embodiment is preferably at least one of Li, Na, and Ag. When the doping element X is at least one of Li, Na, and Ag, hole carriers can be doped.

[0014] (Mg, Sn and doping element molar ratio) In the thermoelectric material according to this embodiment, the molar ratio (Mg:Sn:X) of Mg, Sn, and the doping element X satisfies the following formula (21) or (22) and also satisfies the following formula (23). In the following formulas (21) and (22), α is the ratio α of Mg vacancy defects. Here, when a plurality of doping elements X are included, a is a value based on the total of the doping elements. By the molar ratio of Mg, Sn, and the doping element X in the thermoelectric material according to this embodiment satisfying the following formula (21) or (22) and also satisfying the following formula (23), a higher power factor PF can be obtained and the thermal conductivity can be further reduced. Mg:Sn:X=2×(100-α) / 100:1-a:a...(21) Mg:Sn:X=2×(100-α) / 100-a:1:a...(22) 0 <a≦0.05····(23)

[0015] (Pressure applied element Z) The thermoelectric material according to this embodiment preferably further contains a pressure-applying element Z having an atomic radius smaller than the atomic radius of any one of Mg, Sn, and the doping element X. By containing a pressure-applying element having an atomic radius smaller than the atomic radius of any one of Mg, Sn, and the doping element X, the lattice constant can be reduced and pressure can be applied to the thermoelectric material. This can reduce the energy required to form Mg vacancy defects, and by introducing more Mg vacancy defects, the thermal conductivity of the thermoelectric material can be further reduced.

[0016] The pressure-applying element Z in the thermoelectric material according to this embodiment is preferably at least one of B, Li, Na, Cu, Zn, Ge, and Ag. By using at least one of B, Li, Na, Cu, Zn, Ge, and Ag as the pressure-applying element Z, the thermal conductivity can be further reduced. B is particularly preferable as the pressure-applying element Z.

[0017] (molar ratio of Mg, Sn, doping element X, and pressure applying element Z) In the thermoelectric material according to the present embodiment, the molar ratio (Mg:Sn:X:Z) of Mg, Sn, doping element X, and pressure applying element Z satisfies any one of the following formulae (24) to (27) and also satisfies the following formula (28). In the following formulae (24) to (27), α is the ratio α of Mg vacancy defects. Here, when the thermoelectric material contains a plurality of doping elements X, a is a value based on the total of the doping elements X. When the thermoelectric material contains a plurality of pressure applying elements Z, b is a value based on the total of the pressure applying elements Z. When the molar ratio of Mg, Sn, doping element X, and pressure applying element Z in the thermoelectric material according to the present embodiment satisfies any one of the following formulae (24) to (27) and also satisfies the following formula (28), the thermal conductivity can be further reduced. Mg:Sn:X:Z=2×(100-α) / 100:1-ab:a:b (24) Mg:Sn:X:Z=2×(100-α) / 100-ab:1:a:b (25) Mg:Sn:X:Z=2×(100-α) / 100-a:1-b:a:b...(26) Mg:Sn:X:Z=2×(100-α) / 100-b:1-a:a:b (27) 0 <a≦0.05、0<b≦0.05···(28)

[0018] The thermoelectric material according to this embodiment may be composed of Mg, Sn, a doping element X, and an impurity. The thermoelectric material according to this embodiment may be composed of Mg, Sn, a doping element X, a pressure applying element Z, and an impurity. The impurities are not limited to those contained in the raw materials, but also include those mixed in during the manufacturing process. The thermoelectric material according to this embodiment may contain impurities within a range in which the effects of the present invention can be obtained.

[0019] The chemical composition of the thermoelectric material according to this embodiment is measured by a combination of single crystal X-ray diffraction, inductively coupled plasma mass spectrometry, energy dispersive X-ray spectrometry, neutron diffraction, etc., and the molar ratio can be determined by complementary judgment from the contents of each element obtained by these measurement methods. For example, when the thermoelectric material is composed of Mg, Sn, Sb, and B, the contents can be determined by the following method. The Mg content is measured by single crystal X-ray diffraction and inductively coupled plasma mass spectrometry, the Sn content is measured by inductively coupled plasma mass spectrometry and energy dispersive X-ray spectrometry, the Sb content is measured by inductively coupled plasma mass spectrometry and energy dispersive X-ray spectrometry, and B is measured by neutron diffraction and inductively coupled plasma mass spectrometry. The molar ratio of each element is determined complementarily from the obtained results.

[0020] (Single crystal body consisting of a single crystal) The thermoelectric material according to this embodiment is a single crystal body made of a single crystal. By making the thermoelectric material a single crystal body made of a single crystal, high carrier mobility can be obtained. In addition, the single crystal region and the V MgA semi-coherent interface is formed between the two regions. This semi-coherent interface does not affect the conduction of carriers, but can increase phonon scattering. Therefore, if the thermoelectric material is a single crystal, the thermal conductivity can be reduced. Whether or not it is a single crystal can be determined by the back reflection Laue method using X-rays.

[0021] (Mg vacancy defect ratio α: over 0% and up to 20.0%) In the thermoelectric material according to this embodiment, the ratio α of Mg vacancy defects is more than 0% and not more than 20.0%. By having the ratio α of Mg vacancy defects be more than 0% and not more than 20.0%, it is possible to increase phonon scattering. This makes it possible to reduce the thermal conductivity of the thermoelectric material. The ratio α of Mg vacancy defects is more preferably 8.9% to 18.0%. The ratio α of Mg vacancy defects is even more preferably 12.0% to 18.0%.

[0022] The ratio of Mg vacancy defects can be measured, for example, by the following method. Microcrystals measuring tens of micrometers or less are taken from the thermoelectric material. Single crystal X-ray diffraction is performed on the obtained crystals. Single crystal structure analysis is performed using the diffraction intensity and measurement angle information obtained from the X-ray diffraction to determine the occupancy rates of Mg and Sn. If there are defects (vacancy defects), the occupancy rate of Mg or Sn will be below 100%. The amount of defects, α%, is taken as the amount of Mg vacancy defects or Sn vacancy defects (ratio of Mg or Sn vacancy defects).

[0023] (Seebeck coefficient S) When the thermoelectric material is p-type, the Seebeck coefficient S of the thermoelectric material according to this embodiment at 650K is preferably 80 (μV / K) to 200 (μV / K). When the thermoelectric material is n-type, the Seebeck coefficient S of the thermoelectric material according to this embodiment at 650K is preferably -200 (μV / K) to -80 (μV / K). The Seebeck coefficient S can be measured by a steady-state direct current method using a thermoelectric performance measuring device (for example, RZ200li manufactured by OZAWA Scientific).

[0024] (Conductivity σ) When the thermoelectric material is p-type, the electrical conductivity σ of the thermoelectric material according to this embodiment at 650 K is preferably 500 (S / cm) to 2000 (S / cm). When the thermoelectric material is n-type, the electrical conductivity σ of the thermoelectric material according to this embodiment at 650 K is preferably 500 (S / cm) to 2000 (S / cm). The electrical conductivity σ can be measured by a DC four-terminal method using a thermoelectric performance measuring device (for example, RZ200li manufactured by OZAWA Scientific).

[0025] (Thermal conductivity κ) When the thermoelectric material is p-type, the thermal conductivity κ of the thermoelectric material according to this embodiment at 650K is preferably 2 (W / Km) to 4.7 (W / Km). When the thermoelectric material is n-type, the thermal conductivity κ of the thermoelectric material according to this embodiment at 650K is preferably 2 (W / Km) to 4.7 (W / Km). The thermal conductivity κ can be measured by a laser flash method using a thermal constant measuring device (for example, TC-7000H manufactured by ULVAC-RIKO).

[0026] (carrier density n) When the thermoelectric material is a p-type, the carrier density n at 300 K of the thermoelectric material according to this embodiment is 0.5 (10 20 ×cm -3 )~3.5(10 20 ×cm -3 When the thermoelectric material is an n-type, the carrier density n at 300 K of the thermoelectric material according to this embodiment is preferably 0.5 (10 20 ×cm -3 )~3.5(10 20 ×cm -3 The carrier density n can be calculated from the Hall coefficient obtained by the Hall effect measurement method using a physical property measuring device (for example, PPMS manufactured by Quantum Design), the elementary charge, and the electrical conductivity.

[0027] (Carrier mobility μ) When the thermoelectric material is a p-type, the carrier mobility μ of the thermoelectric material according to this embodiment at 300 K is 50 (cm 2 / Vs)~150(cm 2When the thermoelectric material is an n-type, the carrier mobility μ of the thermoelectric material according to this embodiment at 300 K is preferably 50 (cm 2 / Vs)~150(cm 2 / Vs) is preferable. The carrier mobility μ can be calculated from the Hall coefficient obtained by the Hall effect measurement method using a physical property measurement device (for example, PPMS manufactured by Quantum Design), the elementary charge, and the electrical conductivity.

[0028] (Power factor PF) When the thermoelectric material is p-type, the power factor PF of the thermoelectric material according to this embodiment at 650 K is 1 (10 -3 ×W / K 2 m)~5.5(10 -3 ×W / K 2 When the thermoelectric material is an n-type, the power factor PF of the thermoelectric material according to this embodiment at 650 K is preferably 1 (10 -3 ×W / K 2 m)~5.5(10 -3 ×W / K 2 The power factor PF can be calculated from the Seebeck coefficient S and the electrical conductivity σ.

[0029] (Dimensionless figure of merit zT) When the thermoelectric material is p-type, the dimensionless figure of merit zT of the thermoelectric material according to the present embodiment at 650 K is preferably greater than 0.2. When the thermoelectric material is n-type, the dimensionless figure of merit zT of the thermoelectric material according to the present embodiment at 650 K is preferably greater than 0.5. The dimensionless figure of merit zT can be calculated from the Seebeck coefficient S, the electrical conductivity σ, the thermal conductivity κ, and the absolute temperature T.

[0030] <Method of manufacturing thermoelectric materials> An example of a method for producing a thermoelectric material according to this embodiment will be described. In the method for producing a thermoelectric material according to this embodiment, at least Mg, Sn, and a doping element X for doping a carrier are mixed to prepare a mixture (mixing step), and then the mixture is heated in an inert gas until the temperature of the mixture reaches the melting temperature, thereby melting the mixture (melting step). After melting the mixture, the pressure p [atm] of the inert gas satisfies the following formula (29), and the mixture is cooled so that the average cooling rate from the melting temperature to the slow cooling stop temperature is 10.0° C. / h or less (cooling step). Each step will be described below. 0≦p≦48 (29)

[0031] (Mixing process) In the mixing step according to this embodiment, at least Mg, Sn, and a doping element X for doping the carrier are mixed to prepare a mixture.

[0032] "mixture" The mixture contains at least Mg, Sn, and a doping element X that dopes the carrier.

[0033] The doping element X in the mixture is preferably at least one of Cu, Y, In, Sb, Bi, and La. When the doping element X is at least one of Cu, Y, In, Sb, Bi, and La, it is possible to dope the electron carriers.

[0034] The doping element X in the mixture is preferably at least one of Li, Na, and Ag. Since the doping element X is at least one of Li, Na, and Ag, hole carriers can be doped.

[0035] It is preferable that the molar ratio (Mg:Sn:X) of Mg, Sn, and the doping element X in the mixture satisfies the following formula (30) or (31), and also satisfies the following formulas (32) and (33). Here, when the mixture contains a plurality of doping elements X, a is a value based on the total of the doping elements. By the molar ratio of Mg, Sn, and the doping element X in the mixture satisfying the following formula (30) or (31), and also satisfying the following formulas (32) and (33), the ratio α of Mg vacancy defects can be controlled more precisely. Mg:Sn:X = d:1 - a:a (30) Mg:Sn:X = da:1:a (31) 1.8≦d≦2.2 (32) 0 <a≦0.05····(33)

[0036] The mixture preferably further contains a pressure-applying element Z having an atomic radius smaller than the atomic radius of any one of Mg, Sn, and the doping element X. By containing the pressure-applying element Z in the mixture, the ratio α of vacancy defects of Mg can be more precisely controlled.

[0037] The pressure application element Z in the mixture is preferably at least one of B, Li, Na, Cu, Zn, Ge, and Ag. By using at least one of B, Li, Na, Cu, Zn, Ge, and Ag as the pressure application element Z, it becomes easier to control the ratio α of Mg vacancy defects. The more preferred pressure application element Z is B.

[0038] When the mixture contains a pressure-applying element Z, it is preferable that the molar ratio (Mg:Sn:X:Z) of Mg, Sn, doping element X, and pressure-applying element Z in the mixture satisfies any one of the following formulas (34) to (37), and also satisfies the following formulas (38) and (39). Here, when the mixture contains a plurality of doping elements X, a is a value based on the total of doping elements X. When the mixture contains a plurality of pressure-applying elements Z, b is a value based on the total of pressure-applying elements Z. When the molar ratio of Mg, Sn, doping element X, and pressure-applying element Z in the mixture satisfies any one of the following formulas (34) to (37), and also satisfies the following formulas (38) and (39), the ratio α of Mg vacancy defects can be controlled more precisely. Mg:Sn:X:Z=d:1-ab:a:b (34) Mg:Sn:X:Z=dab:1:a:b (35) Mg:Sn:X:Z=da:1-b:a:b (36) Mg:Sn:X:Z=db:1-a:a:b (37) 1.8≦d≦2.2 (38) 0 <a≦0.05、0<b≦0.05···(39)

[0039] The mixture is obtained by weighing and mixing the grains or powders of each element. The mixing method is not particularly limited, and for example, they may be mixed in a mortar. The purity of each element is preferably 4N or more.

[0040] (Melting process) In the melting step according to the present embodiment, the mixture is melted by heating in an inert gas until the temperature of the mixture reaches the melting temperature. The melting temperature is preferably 1363K to 1042K.

[0041] The melting step may be carried out, for example, by filling a Tammann tube with the mixture and then inserting the Tammann tube into a quartz tube. In this case, an inert gas (e.g., Ar gas) is filled in. The rate of temperature rise to the melting temperature is not particularly limited, but it is preferable to control the rate so as not to cause overshoot.

[0042] (cooling process) In the cooling step according to this embodiment, after the mixture is melted, the mixture is cooled so that the pressure p [atm] of the inert gas satisfies the above formula (29) and the average cooling rate from the melting temperature to the slow-cooling stop temperature is 10.0°C / h or less.

[0043] In the cooling step, the pressure p [atm] of the inert gas satisfies the above formula (29). When the pressure p of the inert gas satisfies the above formula (29), the ratio of vacancy defects in Mg can be improved, and the thermal conductivity of the thermoelectric material can be reduced. It is more preferable that the pressure p of the inert gas satisfies the following formula (40). When the pressure p of the inert gas satisfies the following formula (40), the ratio α of vacancy defects in Mg can be improved, and the thermal conductivity can be further reduced. It is even more preferable that the pressure p of the inert gas satisfies the following formula (41). It is even more preferable that the pressure p of the inert gas satisfies the following formula (42). The pressure p of the inert gas may be controlled from the melting step. 0.6≦p≦48 (40) 1.3≦p≦48 (41) 1.6≦p≦48 (42)

[0044] The slow cooling stop temperature in the cooling step is preferably 1041 K to 973 K. If the slow cooling stop temperature is in this range, the ratio α of vacancy defects in Mg can be improved, and the thermal conductivity can be further reduced. Note that the slow cooling stop temperature may be lower than 973 K.

[0045] In the cooling step, the average cooling rate from the melting temperature to the cooling stop temperature after melting is 10.0°C / h or less. By having an average cooling rate of 10.0°C / h or less, the crystallinity of the thermoelectric material can be made into a single crystal. More preferably, the average cooling rate is 2.5°C / h or less.

[0046] The technical scope of the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention. EXAMPLES

[0047] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0048] Example 1 Mg (particle size 4 mm, purity 4N), Sn powder (particle size 63 μm or less, purity 4N), and Sb (particle size 150 μm pass, purity 5N) were weighed and mixed so that the molar ratio (Mg:Sn:Sb) was 2:0.99:0.01. Here, Sb was added as a doping element. The resulting mixture was filled into a Tammann tube (purity 4N), and the Tammann tube was filled into a quartz tube. At this time, Ar was filled, and the Ar pressure (Ar partial pressure) was controlled to 1.6 atm. The mixture was melted at 1093 K and slowly cooled to 973 K over 48 hours. Thereafter, it was cooled to room temperature and the thermoelectric material of Example 1 (Mg2(Sn 0.99 Sb 0.01 )) was obtained.

[0049] Example 2 Mg (particle size 4 mm, purity 4N), Sn powder (particle size 63 μm or less, purity 4N), Sb (particle size 150 μm pass, purity 5N), and B (particle size 45 μm pass, purity 2N) were weighed and mixed so that the molar ratio (Mg:Sn:Sb:B) was 1.995:0.99:0.01:0.005. Here, Sb was added as a doping element, and B was added as a pressure application element. The obtained mixture was filled into a Tammann tube, and the Tammann tube (purity 4N) was filled into a quartz tube. At this time, Ar was filled and the Ar pressure (Ar partial pressure) was controlled to 1.6 atm. The mixture was melted at 1093 K and slowly cooled to 973 K over 48 hours. Thereafter, it was cooled to room temperature and the thermoelectric material of Example 2 ((Mg 1.995 B 0.005)(Sn 0.99 Sb 0.01 )) was obtained.

[0050] Comparative Example 1 Mg (particle size 4 mm, purity 4N) and Sn powder (particle size 63 μm or less, purity 4N) were weighed and mixed so that the molar ratio (Mg:Sn) was 2:1. The resulting mixture was filled into a Tammann tube, and the Tammann tube was filled into a quartz tube. At this time, Ar was filled and the Ar pressure (Ar partial pressure) was controlled to 1.6 atm. The mixture was melted at 1093 K and slowly cooled to 973 K over 48 hours. It was then cooled to room temperature to obtain the thermoelectric material (Mg2Sn) of Comparative Example 1.

[0051] (Seebeck coefficient S) The Seebeck coefficients S (μV / K) of the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 were measured by the following method. -3 Measurements were carried out by the steady-state direct current method using a thermoelectric performance measuring device (RZ2001i manufactured by OZAWA Scientific) at a temperature of 300K to 650K (MPa) and a measurement temperature of 300K to 650K. The results are shown in Table 1. The results in Table 1 are values ​​at 650K.

[0052] (Conductivity σ) The conductivity σ (S / cm) of the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 was measured by the following method. -3 Measurements were carried out using a thermoelectric performance measuring device (RZ2001i manufactured by OZAWA Scientific) at a temperature of 300K to 650K, using a DC four-terminal method. The results are shown in Table 1. The results in Table 1 are for values ​​at 650K.

[0053] (Thermal conductivity κ) The thermal conductivity κ (W / Km) of the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 was measured by the following method. -3 Measurements were carried out by the laser flash method using a thermal constant measuring device (TC-7000H manufactured by ULVAC-RIKO) at a temperature of 300K to 650K. The results are shown in Table 1. The results in Table 1 are values ​​at 650K.

[0054] (Carrier density n and carrier mobility μ) The carrier density n(10 20 ×cm -3 ) and carrier mobility (cm 2 / Vs) was measured by the following method. The sample size was 2.5 mm × 6 mm × 0.8 mm, and the measurements were performed in a vacuum (up to 1 Pa), at a measurement temperature of 300 K, in a magnetic field range of -5 T to 5 T, using a physical property measuring device (Quantum Design PPMS) and the Hall effect measurement method. The carrier density n and carrier mobility μ were measured using the Hall coefficient R H and the elementary charge e were used to calculate from the following equations (43) and (44). The results are shown in Table 1. The results in Table 1 are values ​​at 300K. n = |1 / (eR H )|···(43) μ = σR H (44)

[0055] (Power factor PF and dimensionless figure of merit zT) The power factor PF and dimensionless figure of merit zT of the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 were calculated using the following formulas (45) and (46). In formulas (45) and (46), S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the thermal conductivity. The results are shown in Table 1. The results in Table 1 are values ​​at 650K. zT=S 2 σT / κ (45) PF=S 2 σ (46)

[0056] (Determination of single crystallinity) The crystallinity of the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 was determined by the back reflection Laue method using X-rays, using a curved IPX diffraction apparatus (Rigaku Corporation, RINT-IP / S). The results are shown in Table 1.

[0057] (Ratio of Mg vacancy defects) The ratio of Mg vacancy defects in the thermoelectric materials of Examples 1 and 2 and Comparative Example 1 was measured as follows. Small crystals with a size of several tens of micrometers or less were collected from the thermoelectric materials of Examples 1 and 2 and Comparative Example 1. Single crystal X-ray diffraction was performed on the obtained crystals. Single crystal structure analysis was performed using the diffraction intensity and measurement angle information obtained by X-ray diffraction to determine the occupancy rates of Mg and Sn. If there is a defect (vacancy defect), the occupancy rate of Mg or Sn falls below 100%. The average defect amount α% was taken as the amount of Mg vacancy defects or Sn vacancy defects. The obtained results are shown in Table 1. In the case of Mg2Sn in Comparative Example 1, the molar ratio (Mg:Sn) of the thermoelectric material is 1.76:1. In the case of Example 1, the molar ratio (Mg:Sn:Sb) of the thermoelectric material is 1.822:0.99:0.01. In the case of Example 2, the molar ratio (Mg:Sn:Sb:B) of the thermoelectric materials is 1.747:0.99:0.01:0.005.

[0058] [Table 1]

[0059] As shown in Table 1, the thermoelectric materials of Examples 1 and 2 satisfied the requirements of the present invention, and therefore had a high power factor PF and a low thermal conductivity κ, and therefore a high dimensionless figure of merit zT. On the other hand, the thermoelectric material of Comparative Example 1 did not satisfy the requirements of the present invention, and therefore had a low PF and an inferior dimensionless figure of merit zT. [Industrial Applicability]

[0060] The thermoelectric material according to this embodiment has both a high power factor PF and low thermal conductivity, and has an excellent dimensionless figure of merit zT, and therefore has high industrial applicability.

Claims

1. Mg, Sn, A doping element X for doping the carrier; Contains It is a single crystal body consisting of a single crystal, The ratio α of the Mg vacancy defects is 8.9% or more and 18.0% or less, Further containing a pressure applying element Z having an atomic radius smaller than the atomic radius of any one of the Mg, Sn, and doping element X, The pressure-applying element Z is at least one of B, Li, Na, Cu, Zn, Ge, and Ag.

2. 2. The thermoelectric material of claim 1, wherein the doping element X is at least one of Cu, Y, In, Sb, Bi, and La.

3. 2. The thermoelectric material of claim 1, wherein the doping element X is at least one of Li, Na, and Ag.

4. The thermoelectric material according to claim 1, wherein a molar ratio (Mg:Sn:X:Z) of the Mg, the Sn, the doping element X, and the pressure application element Z satisfies any one of the following formulas (4) to (7), and also satisfies the following formula (8): Mg:Sn:X:Z=2×(100-α) / 100:1-ab:a:b...(4) Mg:Sn:X:Z=2×(100-α) / 100-ab:1:a:b...(5) Mg:Sn:X:Z=2×(100-α) / 100-a:1-b:a:b...(6) Mg:Sn:X:Z=2×(100-α) / 100-b:1-a:a:b...(7) 0<a≦0.05, 0<b≦0.05...(8)

5. Mg, Sn, A doping element X for doping the carrier; After mixing at least the above to prepare a mixture, Melting the mixture by heating the mixture in an inert gas until the temperature of the mixture reaches a melting temperature; After the mixture is melted, the pressure p [atm] of the inert gas satisfies the following formula (9), and the temperature of the mixture is cooled at an average cooling rate from the melting temperature to a slow cooling stop temperature of 2.5 K / h or more and 10.0 K / h or less; The mixture further contains a pressure-applying element Z having an atomic radius smaller than the atomic radius of any one of the Mg, the Sn, and the doping element X; The pressure-applying element Z is at least one of B, Li, Na, Cu, Zn, Ge, and Ag. 1.3≦p≦48 (9)

6. 6. The method for producing a thermoelectric material according to claim 5, wherein the doping element X is at least one of Cu, Y, In, Sb, Bi, and La.

7. The method for producing a thermoelectric material according to claim 5 , wherein the doping element X is at least one of Li, Na, and Ag.

8. 6. The method for producing a thermoelectric material according to claim 5, wherein a molar ratio (Mg:Sn:X:Z) of the Mg, the Sn, the doping element X, and the pressure applying element Z satisfies any one of the following formulas (14) to (17), and also satisfies the following formulas (18) and (19): Mg:Sn:X:Z=d:1-ab:a:b...(14) Mg:Sn:X:Z=d-a-b:1:a:b...(15) Mg:Sn:X:Z=da:1-b:a:b...(16) Mg:Sn:X:Z=d-b:1-a:a:b...(17) 1.8≦d≦2.2 (18) 0<a≦0.05, 0<b≦0.05... (19)

9. The method for producing a thermoelectric material according to any one of claims 5 to 8, wherein the melting temperature is from 1363K to 1042K.

10. The method for producing a thermoelectric material according to any one of claims 5 to 9, wherein the slow cooling stop temperature is 1041K to 973K.

11. The method for producing a thermoelectric material according to any one of claims 5 to 10, wherein the pressure p satisfies the following formula (20): 1.6≦p≦48 (20)

Citation Information

Patent Citations

  • Method for manufacturing a device for direct thermoelectric energy conversion

    JP2005503025A

  • Mg INTERMETALLIC COMPOUND, AND DEVICE APPLYING THE SAME

    JP2008160077A

  • Quaternary magnesium-tin compound and thermoelectric conversion element using the same

    JP2010031322A

  • Mg INTERMETALLIC COMPOUND, AND DEVICE APPLYING THE SAME

    JP2010050185A

  • Thermoelectric material and method of producing the same

    JP2011151329A